Polski James Dean? Młody gniewny? Fenomen Marka Hłaski i badania transnarodowe - Galant, Jan (Załącznik Kulturoznawczy, 2024)
The article contains a proposal to interpret the work and legend of Marek Hłasko in the transnational context of social and cultural changes in Europe and the world of the mid-1950s. The starting point is the commonly perceived and established in colloquial phraseology similarity of the Polish writer's image to the myth of James Dean and of his works to the literature of the British Young Angry Men. This allows us to ask about the relationship between the characters' class affiliation and consciousness and their image of masculinity, the new model of family life presented, and the role of the author’s tragic death in shaping the artistic legend. What constitutes the methodological framework of the analysis, is the concept of transnational research (transnational turn in literary studies), focusing on the analysis of intercultural connections and flows, while the historical, literary and cultural background is provided by the idea of Cold War culture as a transnational community of experience, which makes it possible to perceive and explain the fact of cultural analogies, similarities and convergences on both sides of the Iron Curtain. The conclusion of the article is that, seen in a transnational context, Hłasko's work and biography represent the most characteristic features and themes of Cold War culture: the experience of the Iron Curtain and migration, the bipolarity of the world, the fear of nuclear conflict, the expansion of popular culture.